Aksara Jawa: Do the Javanese Students can Read and Write It? - Karimah, Azzahrotul (TALENTA Publisher, 2022)
The Javanese language is one of the languages used by people in Indonesia. However, one issue arises when many people speak in Javanese while only a few people can read and write in the alphabet of the Javanese, which is called Aksara Jawa. This Aksara Jawa is mainly used to write Javanese. In its development, it is also used to write several other regional languages, such as Sundanese, Madurese, Sasak, and Malay, as well as historical languages, such as Sanskrit and Kawi. The Javanese script is a derivative of the Indian Brahmi script through the Kawi script and is closely related to the Balinese script. The Javanese script was actively used in Javanese literature and daily writing from the mid-15th century to the mid-20th century before being replaced by Latin letters. Nowadays, 21st century, the Aksara Jawa is learned by students at school as a local language lesson. Some schools provide it while the rest is not. A question comes out; do the Javanese generations (students) nowadays can write and read the Aksara Jawa? The result shows that in many elementary schools until junior high school, students cannot read and write in Aksara Jawa.